Comparative analysis on adaptive features for RFID middleware - Mohd. Hashim, Siti Zaiton; Mardiyono, Mardiyono; Anuar, Nurulhaini; Wan Kadir, Wan Mohd. Nasir (2008)

(untitled)
Middleware is software that connects between hardware and application layer. Traditional middleware is limited in its ability to support adaptation while adaptive middleware enables modifying its behavior to conform to new situation. RFID applications grow widely and are used in many purposes such as supply chain management and ubiquitous computing enabled by pervasive, low cost sensing and identification. Implementing adaptive characteristic in RFID middleware will increase the capability of adaptation to specific environment such as different reader/tag, different application, and different platform. Adaptive middleware enables modifying the behavior of a distributed application after the application is developed in response to some changes in functional requirements or operating conditions. An extensive study has been carried out, and comparative analysis has been done on identifying the standard features that reflect the functionalities of RFID middleware and adaptive features that represent the non-functionalities of RFID middleware address to overcome the specific problems of application systems. This paper discusses the outcome of this study and adaptive middleware architecture for RFID applications is proposed that supports multi readers and multi applications.